The plant coumarins auraptene and lacinartin as potential multifunctional therapeutic agents for treating periodontal disease - Marquis Annie; Genovese Salvatore; Epifano Francesco; Grenier Daniel (BMC, 2012)
Abstract Background Periodontal diseases are bacterial infections leading to chronic inflammation disorders that are frequently observed in adults. In the present study, we evaluated the effect of auraptene and lacinartin, two natural oxyprenylated coumarins, on the growth, adherence properties, and collagenase activity of Porphyromonas gingivalis. We also investigated the capacity of these compounds to reduce cytokine and matrix metalloproteinase (MMP) secretion by lipopolysaccharide (LPS)-stimulated macrophages and to inhibit MMP-9 activity. Methods Microplate dilution assays were performed to determine the effect of auraptene and lacinartin on P. gingivalis growth as well as biofilm formation stained with crystal violet. Adhesion of FITC-labeled P. gingivalis to oral epithelial cells was monitored by fluorometry. The effects of auraptene and lacinartin on LPS-induced cytokine and MMP secretion by macrophages were determined by immunological assays. Fluorogenic assays were used to evaluate the capacity of the two coumarins to inhibit the activity of P. gingivalis collagenase and MMP-9. Results Only lacinartin completely inhibited P. gingivalis growth in a complex culture medium. However, under iron-limiting conditions, auraptene and lacinartin both inhibited the growth of P. gingivalis. Lacinartin also inhibited biofilm formation by P. gingivalis and promoted biofilm desorption. Both compounds prevented the adherence of P. gingivalis to oral epithelial cells, dose-dependently reduced the secretion of cytokines (IL-8 and TNF-α) and MMP-8 and MMP-9 by LPS-stimulated macrophages, and inhibited MMP-9 activity. Lacinartin also inhibited P. gingivalis collagenase activity. Conclusions By acting on multiple targets, including pathogenic bacteria, tissue-destructive enzymes, and the host inflammatory response, auraptene and lacinartin may be promising natural compounds for preventing and treating periodontal diseases.